The Impact of a Possible Trump Reelection on Mexican Immigration Pressures in Alternative Countries - Michel Beine; Michel Bierlaire; Evangelos Paschalidis; Silvia Varotto; Andreas B. Vortisch (CESifo GmbH, 2024)
We address the question of the impact of a possible Trump reelection on the location choices of potential Mexican migrants. We use migration aspiration data from the Gallup World Poll Surveys which provide the preferred location choices of Mexican respondents before, during and after the Trump Presidency. We show that Trump presidency led to an increase in disapproval rates about the US leadership among Mexican respondents, which in turn led to a reduced level of attractiveness of the US location. Using a Cross-Nested Logit model that allows to account for the heterogeneity in the substitution patterns between alternative locations to the US, we simulate the impact of a possible reelection of Donald Trump based on different scenarios about these dis-approval rates. We find that such a reelection would lead to an increase in the number of stayers in Mexico but would also create heterogeneous immigration pressures from Mexico across potential foreign locations. In particular, countries such as Canada, the UK, Germany, Spain, and France would face significantly higher increases in Mexican immigration pressures. We also show that the reelection of Donald Trump would lower the skill content of Mexican potential immigrants in the US and would induce an opposite effect in destinations that are perceived as close substitutes.
Keywords: C25; F22; J61; 330; location choice models; migration aspirations; Mexican immigrants; substitution effects